Effect of cycle ergometer training using different intensities in increasing catecholamine hormone of overweight females - Nining Widyah Kusnanik; Tutur Jatmiko; Rizky Sota Dyaksa; Novadri Ayubi; Cyuzuzo Callixte; Muhammad Aljunaid; Abd. Muin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The main purpose of this study was to compare cycle ergometer training using low intensity and moderate intensity in increasing the catecholamine hormone of overweight females. This study was conducted on 50 overweight females with mean age of 22.44±2.97 years old and body mass index between 25 kg.m.2 to 30 kg.m.2. Treatment was given 4 times per week during 5 weeks periods in Group 1 with low intensity cycle ergometer continuous training (60%-70% HRmax), and Group 2 with moderate intensity cycle ergometer continuous training (70%-80% HRmax). Heart rate was monitored using polar heart rate monitor H10. Pre-test was taken before giving treatment and post-test after giving a treatment by taking blood a day after doing exercise and fasting at night and the blood samples obtained are taken to the laboratory for serum sample analysis. Data were analyzed using paired t-test. The result found that there was an increase in catecholamine hormone in both groups with a p-value of <0.05. It can be concluded that cycle ergometer training using low and moderate-intensity improved catecholamine hormone for overweight females.